Copper and virginiamycin as swine growth promotors - Bellaver, Cláudio; Gomes, Paulo Cezar; Costa, Valdomiro; Fialho, Elias Tadeu; Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out at the Centro Nacional de Pesquisa de Suínos e Aves (CNPSA), at Concórdia, SC, Brazil, between october 81 and january 82, with the objective of quantify the effects of Copper (c) and Virginiamycin (v) utilized as swine growth promotors measuring performance and carcass variables. The rations were based in corn, soybean meal, bicalcium phosphate, limestone and supplemented with minerals and vitamins. C was tested at level of 125 ppm, and V at 10 ppm, in a randomized experimental design, with eight treatments and three replicates with six animals each. C in the level of 125 ppm increased (P<0.05) the animal weight gain until 25 kg. The performance and carcass variables were not affected (P>0.05) at final (139 days) of experimentation. The males had better (P<0.05) weight gain than females, at final, with 538 g vs 443 g, respectively.